A Novel Postbiotic Patch Formulation Using Pediococcus acidilactici BK01 for Anti-Acne Applications - Lidia Armayeni; Rini Agustin; Sri Melia; Adhitya Jessica (Fakultas Farmasi Universitas Andalas, 2026)
Acne is an inflammatory skin disorder often associated with infection by Cutibacterium acnes. Postbiotics in the form of cell-free supernatant (CFS) from Pediococcus acidilactici BK01 contain lactic acid, bacteriocins, and hydrogen peroxide, which exhibit potential antibacterial activity. This study aimed to formulate P. acidilactici BK01 CFS into a topical patch and evaluate its activity against C. acnes. Antibacterial activity and minimum inhibitory concentration (MIC) were determined using the well-diffusion method. The MIC (6.25%) was used to formulate patches via solvent-casting with HPMC K4M or PVA (2–4%) as polymers and glycerin, propylene glycol, or PEG 400 (0.2–0.6%) as plasticizers. The selected formulation was evaluated for antibacterial activity and physical characteristics. A combination of 4% PVA and 0.6% glycerin produced the best base and was used to prepare patches containing 6.25–75% CFS. The 65% CFS patch showed the highest inhibition against C. acnes ATCC 11827 (12.03 ± 0.373 mm), categorized as strong. The patch demonstrated acceptable organoleptic properties, thickness, folding endurance, pH, moisture content, and tensile strength. These findings indicate that the 65% CFS patch has potential as a topical anti-acne preparation.